Quercetin induces p53‐independent cancer cell death through lysosome activation by the transcription factor EB and Reactive Oxygen Species‐dependent ferroptosis - Wang, Zi‐Xuan; Ma, Jing; Li, Xin‐Yu; Wu, Yong; Shi, Huan; Chen, Yao; Lu, Guang; Shen, Han‐Ming; Lu, Guo‐Dong; Zhou, Jing (British journal of pharmacology, 2021)
Background and Purpose Cancer cells exhibit more dependence on iron and enhanced sensitivity to iron‐dependent, programmed cell death (ferroptosis) than normal cells. Quercetin exerts anti‐cancer effects, but the underlying molecular mechanism is largely unknown. In this study, we aimed to investigate the involvement of lysosome function and ferroptosis in the anti‐cancer potential of quercetin. Experimental Approach We used MTT assays and DNA content analysis to evaluate the cytotoxicity, colony formation assay to investigate cell proliferation, and flow cytometry and confocal microscopy to detect lysosomal acidification and protease enzyme activity. Western blotting, cell subfractionation, RT‐PCR and siRNA transfection were used to establish molecular mechanisms of action. Key Results Quercetin is known to promote p53‐independent cell death in various cancer cell lines. Although quercetin induces autophagy, genetic silencing of Atg7 fails to affect quercetin‐induced cell death. In contrast, both lysosome inhibitors and knockdown of the transcription factor EB can prevent quercetin‐induced cell death, suggesting the involvement of lysosome. Next, quercetin is found to induce lysosomal activation sequentially through nuclear translocation of EB and transcriptional activation of lysosomal genes. Notably, quercetin promoted lysosome‐dependent ferritin degradation and free iron release. This action and quercetin‐induced ROS generation synergistically resulted in lipid peroxidation and ferroptosis. Furthermore, Bid may link ferroptosis with apoptosis to cause cell death. Conclusion and Implications Quercetin induced EB‐mediated lysosome activation and increased ferritin degradation leading to ferroptosis and Bid‐involved apoptosis. Results from this study may expand our current knowledge about the mechanism of quercetin as an anti‐cancer agent.